Personality traits and nonverbal communication skills of Malaysian TESL trainee practitioners - Abdul Sitra, Abdul Rashid; Abdullah, Ain Nadzimah (Universiti Putra Malaysia Press, 2017)
Effective TESL trainee practitioners (TPs) not only equip themselves with the knowledge of the English language but must also have the right personality traits to suit their profession. Their personality needs to be further complemented with the proper use of nonverbal communication skills. This study investigates TPs’ self-reported use of nonverbal communication skills and the dominant personality traits of TPs. In addition, this study investigates the relationship between TESL trainee practitioners’ personality traits and their nonverbal communication skills. The Big Five personality traits measured in this study include openness, agreeableness, conscientiousness, neuroticism, and extraversion, while the nonverbal communication skills measured are facial expression, eye contact, posture, touch, proxemics, paralanguage, clothing, gestures, and chronemics. Data was collected through two sets of questionnaires given to 277 trainee practitioners from the TESL programmes in four teacher training institutes in Malaysia. Findings suggest that TPs are concerned about their attire during working hours, and agreeableness is their dominant personality trait. Out of the five personality traits, only three - agreeableness, openness, and neuroticism - showed significant relationships with nonverbal communication. Implications for these correlations are discussed. The salience of personality traits in relation to nonverbal communication skills of trainee teachers are further discussed as relevant characteristics in developing the skills of effective teaching. These characteristics are particularly recommended to be included in the ongoing reflective practices of teachers for awareness and self-improvement.